Computer Vision Technologies in Controlling the Electric Drive of Railway Transport - Yaroslav Kyrylenko; Yurij Kutovoj; Tatiana Kunchenko; Oleksandr Nesterenko (Communications)
Analysis of statistical data on accidents on railways shows that most often an accident occurs due to the influence of the human factor, obstacles on the track, curvature of the track, the phenomenon of skidding and slipping in dynamic modes. The novelty of the proposed work consists in development of a mathematical model and a study of the automatic speed control, depending on the curvature of the track or in the presence of obstacles, and track defects, as well as measuring the linear speed of the railway transport as one of the main elements of the slip protection system and the system for implementing the maximum traction force. The solution of these problems is possible with the help of a multipurpose sensor, which is a video camera, to form the feedback signals to the control system.